Pengaruh Celebrity Endorser Dan Social Media Terhadap Minat Beli - Erliyantina, Mutiara; Fadillah, Adil (Jurnal Informatika Kesatuan, 2022)
Nowadays we have entered the digital world, everything possible can be controlled from any place through the internet network with gadget devices / smartphones. It makes it easier for human mobility in daily activities including in the business world, especially in the field of creative economy, so that this phenomenon further strengthens the world towards the direction of the digital economy. For example, we are simply familiar with email, website usage, applications, online product management, and online transactions. The purpose of this study is to analyze the Influence of Celebrity Endorser And Social Media On The Interests of Buying Case Studies On Tokopedia. The purpose of this research is to analyze the influence of Celebrity Endorser tehadap Buy Interest on Tokopedia. To analyze the influence of Social Media on Buying Interests on Tokopedia.And To analyze the social influence of edia and Celebrity Endorser on Buying Interests on Tokopedia The number of respondents is 130 respondents taken who use Tokopedia. Processed with SPSS version 25, the results of the study is Celebrity Endorser has a positive and significant influence on Tokopedia's Buying Interest. Celebrity Endorser has a significant positive effect on Buying Interest indicated by the value of β = 0.184 and p value or sig. = 0.000, Social Media has a positive and significant influence on Tokopedia's Buying Interest. Social Media has a significant positive effect on Buying Interest indicated by the value of β = 0.783 and p value or sig. = 0.021, Celebrity Endorser and Social Media together have a positive and significant influence on Tokopedia's Buying Interests. Based on the test table F obtained the value of F count of 49,668 and table F of 3.07 thus F count greater than F table or (61,862 > 3.07). The R-Square value is 65.9% while the rest is explained by other variables. Keywords: Social Media, Celebrity Endorser, Buying Interest